Mulheres em tempos de pandemia - Brabo, Tânia Suely Antonelli Marcelino (Editora Oficina Universitária, 2023)
The Living Women Network (RMV) has the mission to prevent and intervene in violence against women, as a political and ideological position. In view of the nature of the Mulheres Vivas Network and its ideology, researchers from several countries and institutions discussed the bases and functioning of the Network embodied in a text entitled "Manifesto of the Network" (attached). In this perspective, it has promoted the Seminars of the Living Women Network, with the aim of contributing to the reduction of violence against women and giving visibility to this serious problem experienced even today by many women. In 2021, the II Seminar of the Mulheres Vivas Network opened the possibility for other researchers to present works derived from ongoing or completed research and, in this sense, invited them to participate in this book with their research in chapter format. The theme of the II Seminar was "Women in times of a pandemic" with the aim of reflecting on the problems experienced by women considering the diversity of gender, race/ethnicity and class in this serious moment of pandemic, considered a global public health problem.